WARDAH'S BRAND IMAGE THROUGH INSTAGRAM SOCIAL MEDIA @WARDAHBEAUTY - Bintang Khalishah; Rochmaniah, Ainur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study conducted interviews with ten active users of the Wardah Beauty Instagram account to analyze consumer perceptions of the Wardah brand image built through their content and interactions on the account. Method: This study used a descriptive qualitative approach. Results: The results showed that most respondents had a positive perception of the Wardah brand, which was considered to have a strong image, be halal, and be in line with Indonesian women's values. Consumers are more aware of and trust informative and interesting content, such as makeup tutorials and product reviews, as well as active interactions on social media. The emotional attachment built through personal experiences and positive customer reviews also increases customer loyalty to the brand. According to this study, Wardah must continue to create new content on social media to attract customers and maintain its success in an increasingly competitive beauty industry. The results show that Wardah has successfully created a trustworthy brand image in the eyes of consumers through consistent visual appearance and the ability to establish solid interactions through informative and educational content. Wardah has been able to increase consumer awareness and trust in Wardah products and strengthen long-term loyalty. Novelty: This study highlights the role of consistent visual appearance and interactive, informative social media content in building consumer trust, emotional attachment, and long-term loyalty to a halal beauty brand in Indonesia.